Android N application development - Mondal, Soham; Safari eBooks ([Place of publication not identified] : Packt, 2016)
"Android Nougat is the 7th major version of the Android operating system. Nougat introduces notable changes to the operating system and its development platform, including the ability to display multiple apps on-screen at once in a split-screen view, support for inline replies to notifications, as well as an OpenJDK-based Java environment, support for the Vulkan graphics rendering API, and 'seamless' system updates on supported devices. This course begins with an introduction on Android Nougat. By getting to know all its new features, get started building your own application. Start off by creating its UI with Android's key developer tool the Android Studio and Android SDK. Networking concepts with the API are the next in line, followed by creating an application that will give you a practical hands on experience such as a News Reader Application. Complete the building process by implementing fire base Analytics and Crash Analysis to measure the success and health of your app. Once you've got a good grasp on these concepts, enhance your skills in maintaining hi-quality apps by learning the testing principles. By the end of this course get acquainted on how to publish your application on the Play Store and leverage the well-known, best practices in Android, known typically only to the initiated."--Resource description page.
Presenter, Soham Mondal.
Title from title screen (viewed January 17, 2017).
Date of publication from resource description page.
Keywords: Android (Electronic resource); Application software -- Development; Mobile apps; Electronic books